De-escalating radiotherapy in pathologic complete response oral cancer after neoadjuvant immunochemotherapy: equal survival, better life, and a biomarker guide - Guan, Zhenjie; Yu, Qiongqiong (Frontiers in Oncology, 2026)
BackgroundThe potential to omit adjuvant radiotherapy in patients with locally advanced oral squamous cell carcinoma (OSCC) who achieve a pathological complete response (pCR) after neoadjuvant immunochemotherapy (NICT) remains undefined. This study aimed to evaluate the oncologic safety of a radiotherapy-de-escalation strategy and to identify predictive biomarkers for its success.MethodsIn this retrospective cohort study, pCR patients were categorized into a de-escalation group (n=65) and a standard care group (adjuvant radiotherapy/chemoradiotherapy, n=286). Propensity score matching (PSM) was performed to compare disease-free survival (DFS). Comprehensive genomic and immune profiling was conducted on pre-treatment biopsies from the de-escalation cohort to identify biomarkers associated with recurrence.ResultsAfter 1:1 PSM, DFS was equivalent between the de-escalation and standard care groups (HR 1.25, 95% CI 0.72–2.18; p=0.425). The de-escalation strategy yielded significantly better quality of life and eliminated severe radiation toxicities, albeit with increased immune-related adverse events. Within the de-escalation cohort, multivariate analysis identified TP53 mutation (adjusted HR 4.05, p=0.019) and a low pre-treatment B cell signature score (adjusted HR 2.15 per 1-unit decrease, p=0.010) as independent predictors of worse DFS. A two-biomarker model stratified patients into low-, intermediate-, and high-risk groups with distinct recurrence rates (0%, 17.1%, and 40.0%, respectively; p=0.019).ConclusionAdjuvant radiotherapy omission with maintenance immunotherapy appears to be a safe and patient-beneficial strategy for OSCC patients achieving pCR after NICT. The integrated TP53/B-cell biomarker model provides preliminary evidence for personalizing this de-escalation approach.